Perubahan Tata Ruang dan Fungsi Kampung Akuarium, Jakarta - Ashadi Ashadi; Ratna Dewi Nur'aini; Finta Lissimia; Anisa Anisa; Suriani Ngah Abdul Wahab (Universitas Sebelas Maret Surakarta, 2022)
Kampung Akuarium is one of the historical places in the coastal area of North Jakarta. At the beginning, the area of Kampung Akuarium was dominated by swamps, so houses were built using stilt house construction. The development into a dense settlement which was then carried out evictions in the area and now it has become a residential area with the establishment of flats whose plans consist of 5 blocks. The purpose of this study is to explore in depth the changes that occur (especially regarding the function and spatial structure of the building and the surrounding environment) in Kampung Susun Akuarium. This study uses a qualitative descriptive method with historical and architectural approaches to analyze problems in depth by exploring social and architectural phenomena. from time to time through detailed and in-depth data collection sourced from observations, interviews, documents and object description reports. Changes that occurred in the Kampung Susun Akuarium Jakarta before and after the eviction were found in land function, type of building, spatial planning, building construction, house function, home ownership status, socio-economic conditions, and behavior.